Challenges Faced in the Implementation of the Zimbabwe Agenda for Sustainable Socio-Economic Transformation Economic Policy from 2013 to 2018 - Dr., Alouis Chilunjika; Masiyakurima-January, Patricia; Muzvidziwa-Chilunjika, Sharon (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2020)
A number of policies have been put in place as of 1980 but the implementation of the policy objectives has been highly compromised. This research is therefore premised on exploring the challenges faced in the implementation of economic policies using the Zimbabwe Agenda for Sustainable Socio-Economic Transformation (ZIMASSET) of 2013 to 2018 as the focal point. The study employs a case study research design which triangulates qualitative as well as quantitative research methods into mixed methods. On sampling techniques, the research employs simple random sampling and purposive sampling. Structured questionnaires and in-depth interviews were also used in collecting data. The research established that the ZIMASSET policy has been ruled out as an appetizing economic blueprint which when followed to its logical conclusions can in a way turn around the economic fortunes of the country. Be that as it may, some contend that there is nothing peculiar about the ZIMASSET policy as it is yet another attempt by the ZANU-PF led government to moot a policy that will die a premature death. In light of this, the study recommends policy autonomy, multiplicity of sources of funding, supporting the agricultural sector, curbing corruption, clear policy procedures as well as utmost commitment to the policy as strategies that can enhance the successful implementation of future economic policies in Zimbabwe.